2020
DOI: 10.1002/er.5896
|View full text |Cite
|
Sign up to set email alerts
|

Selection of phase‐change material for thermal management of electronic devices usingmulti‐attributedecision‐making technique

Abstract: Selection of proper phase-change material (PCM) plays a crucial role in the development of latent heat thermal management module. Very often, selection of improper material leads to early failure of the product which results in huge economic loss. Most of the researchers utilize PCM in a particular application based on their experience and availability. The designer needs to consider all possible alternatives and evaluate in terms of various conflicting criteria or attributes. The optimal selection of PCM for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…According to Yang et al [46],"A monotone increasing function defined as ξ: ℜ→ [0, 1] will be called an uncertainty distribution if and only if the function's monotonicity is continuous excluding Θ(x) ≡ 0 and Θ(x) ≡ 1".…”
Section: Theoremmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Yang et al [46],"A monotone increasing function defined as ξ: ℜ→ [0, 1] will be called an uncertainty distribution if and only if the function's monotonicity is continuous excluding Θ(x) ≡ 0 and Θ(x) ≡ 1".…”
Section: Theoremmentioning
confidence: 99%
“…A variable that is uncertain denoted by 𝑍𝑍 (𝑎𝑎, 𝑏𝑏, 𝑐𝑐), with the condition 𝑎𝑎 < 𝑏𝑏 < 𝑐𝑐 for 𝑎𝑎, 𝑏𝑏, 𝑐𝑐 ∈ ℜ, is called zigzag if it is following a zigzag uncertainty distribution: To simplify the use of the zigzag uncertain variable, it has to be converted to equivalent crisp form using the reduction method based on the expected value. In the paper of Yang et al [46], the method of reduction based on the expected value is shown below:…”
Section: Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…They proved that the MCDM algorithm provides the best solution for solving the selection of suitable coating materials to minimize the wear issue. Similarly, Kumar et al [12] used MCDM, i.e., AHP and TOPSIS, for a selection of phase-change material (PCM) in thermal control of electronic components and found that AISI A2 steel is the best option for the mentioned application. In Iran's semi-arid area, two MADM methods have been used to design the best water supply plant.…”
Section: Bakground Literaturementioning
confidence: 99%